Non-ocular risk factors in Turkish children with strabismus and amblyopia - Çakır, Burçin; Aksoy, Nilgün Özkan; Bursalı, Özlem; Özmen, Sedat (The Turkish Journal of Pediatrics, 2022)
Background. To evaluate non-ocular risk factors including family history, febrile seizure, history of trauma, neurological diseases, and prematurity in Turkish children with strabismus and amblyopia. Methods. The records of patients diagnosed with strabismus and/or amblyopia below 18 years old, were recruited. The current mean age, sex, types and subtypes of strabismus and amblyopia, family history, history of trauma, and febrile seizure were investigated. The presence of neurological diseases and prematurity were noted. Family history was investigated whether the presence of strabismus or amblyopia was maternal or paternal. Blood relatives were divided into 3 groups including first, second, and third-degree relatives. The relationship between blood relative degrees and types of strabismus or amblyopia were assessed. Results. There were 803 patients with a current median age of 8 years (1-29 years). Of these patients, 786 patients could be evaluated and 55% had esotropia (ET), 32.6% had exotropia (XT) and 12.5% had amblyopia as a primary diagnosis. Positive family history of strabismus or amblyopia was more common among all risk factors. There was a statistically significant rate of patients with a positive family history in the first-degree relatives, in the esotropic patient group (p= 0.002). Maternal positive family history was more common in patients with refractive ET (p= 0.024) and paternal positive family history was more common in patients with intermittent XT (p= 0.009). Conclusions. The rates of positive family history of amblyopia and strabismus were not statistically different. Family history of strabismus in first-degree relatives of patients with esotropia was markedly high. The family history of strabismus on the maternal or paternal side might be different in patients with different subtypes of strabismus.